Kajian Literatur: Penerapan Blended Project Based Learning Terintegrasi Website Bioenial sebagai upaya meningkatkan Kreativitas Belajar dan Keterampilan Berpikir Kritis - Agus Riyanto; Sarwanto Sarwanto; Bowo Sugiharto (Universitas Sebelas Maret, 2025)
The purpose of this literature review is to explore the effectiveness of the application of Blended Project Based Learning integrated with Bioenial Website as an effort to improve Learning Creativity and Critical Thinking Skills. The research method used is literature review. The literature sources used in this study consist of various journals indexed from Google Scholar and Scopus. The research population is research journals relevant to the topic for various levels of study, from Early Childhood Education to Higher Education. The search criteria were the range of journals from 2019-2024, containing the same keywords as the research topic, and full papers. The results of the journal search by fulfilling the specified inclusion criteria found 960 journals. From this number, 10 journals were obtained that were in accordance with the objectives of this study. It can be concluded that the application of blended learning that integrates innovative and creative elements such as the Project Based Learning model integrated with the Bioenial Website that makes effective use of technology, shows great potential for improving learning creativity and critical thinking skills. However, there are challenges that need to be overcome to achieve optimal results.